Dampak Efektivitas Program Sertifikasi Guru Dalam Meningkatkan Profesionalisme Guru Di Man 2 Model Medan - Zulham Hidayah Pardede (Proceedings of Annual Conference on Islamic Educational Management, 2022)
Professional teachers are required to have a minimum academic qualification of bachelor (S-1) or diploma four (D-IV), master competence, have an educator certificate, be physically and mentally healthy, and the ability to realize national education goals. The fact is, the teachers quality and competence in Indonesia is not as expected. In terms of educational qualifications, from 2.92 million teachers, only about 51% have a Bachelor's degree or more and the rest did not have a Bachelor's degree. Likewise from the certification requirements, only around 70.5% of teachers met the certification requirements. This study aims to determine the Effectiveness of Teacher Certification Programs in Improving Teacher Professionalism in MAN 2 Medan Model. The method used in this research is qualitative research. The data source is interviews with teacher who is certified both PNS and Non-PNS. Based on the results, the certification by MAN 2 Medan is in line with the aim of teacher certification, that is creating professional teachers. In particular, the desired impact shows that teacher certification enhances the ability and competence of teachers in creating an effective learning environment. The teacher more professional in maintaining the timeliness in classroom and starting lessons in accordance with established learning procedures, and discipline in preparing all learning tools. Teacher certification also improved teacher welfare and dignity as a consequence of the benefits of basic salary every month.